Strategi Guru IPS dalam Menanamkan Sikap Nasionalisme Melalui Pembelajaran Sejarah pada Siswa Kelas VII Di SMP Negeri 25 Kota Bengkulu - Nopran hadi; Irwan satria; Nurniswah Nurniswah (JPT : Jurnal Pendidikan Tematik, 2024)
This research aims to find out the strategies of social studies teachers in instilling nationalist attitudes through history learning and to find out the obstacles teachers have in instilling nationalist attitudes through history learning in class VII students at SMP Negeri 25 Bengkulu City. This research is a qualitative research. Data collection techniques use observation, interviews and documentation. The research subjects were social studies teachers at SMP Negeri 25 Bengkulu City. Based on the research results, it is clear that the social studies teacher's strategy in instilling an attitude of nationalism through history learning in class VII students at SMP Negeri 25 Bengkulu City is that the teacher instills an attitude of nationalism using several learning strategies and the teacher instills in the students a sense of love for the country, willingness to sacrifice, unity and oneness, and never give up. The obstacles for social studies teachers in instilling an attitude of nationalism through learning history in class VII students at SMP Negeri 25 Bengkulu City are the lack of allocation of study time, learning media, an attitude of willingness to sacrifice and tolerance.